Control the crystal growth of Al-doped ZnO thin film prepared by pulsed laser deposition and the influences on its optical and electrical properties - N. Khemasiri; S. Jessadaluk; N. Kayunkid; S. Rahong; A. Rangkasikorn; S. Wirunchit; A. Klamchuen; J. Nukeaw (My University, 2017)
In this work, highly transparent and highly conductive thin films of Al-doped ZnO (AZO) are achieved by pulsed laser deposition (PLD). By changing substrate temperature in the range of room temperature to 500°C during the deposition process, the preferential growth direction of AZO crystal is controlled and, therefore, the surface morphology, optical and electrical properties of AZO thin films are able to be manipulated. X-ray diffractograms as a function of the substrate temperature clearly illustrate the ability to control the preferential growth direction of AZO. At the low substrate temperature, the growth along [002] direction corresponding to c-axis of hexagonal ZnO is only observed. By elevating the substrate temperature, not only crystallinity of AZO thin film is further improved but also the competition of crystal growth along the [002], [001] and [101] directions are occurred due to the increase of total energy and surface mobility of cluster/atom. The AZO films obtained by all preparation conditions exhibit an n-type semiconducting characteristics, furthermore, the carrier concentration and the carrier mobility of AZO thin films can be optimized to reach 4.10×1020 cm-3 and 7.53 cm2/Vs, respectively. The excellences in both carrier concentration and mobility of AZO thin film lead to very low resistivity of 2.08×10-3 Ωcm. In addition, the wide optical band gap of ∼3.50 eV together with the high transparency over 90% in visible region is obtained from the AZO thin films. The exceptional optical and electrical properties of AZO thin film demonstrate that such material has enough potential to become a promising candidate using in optoelectronic applications.
Keywords: Pulsed Laser Deposition; Crystal (programming language); Electron Mobility; ZnO doping and properties